Al and Zn co-doped sodium ion battery layered positive electrode material and preparation method thereof
By co-doping Al and Zn on the O3 type positive electrode material of sodium ion battery, the problem of slow Na+ diffusion kinetics and complex phase transition of the material is solved, and the magnification and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411926408.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The O3-type layered positive electrode material of sodium ion battery has slow Na+ diffusion kinetics and complex phase transition problems, resulting in reduced battery capacity attenuation and cycle performance.
By co-doping the bimetal cation of Al and Zn on the O3-type NaNi1/3Fe1/3Mn1/3O2 layered sodium ion battery positive electrode material, Na(Ni1/3Fe1/3Mn1/3)1-2xAlxZnxO2 material was prepared to improve the structural strength and ion diffusion performance of the material.
The rate performance and cycle performance of the positive electrode material of sodium ion battery have been improved. The capacity retention rate of the battery is greater than or equal to 73% after 200 cycles in 1C.
Smart Images

Figure CN119650659A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to an Al and Zn co-doped sodium ion battery layered positive electrode material and a preparation method thereof. Background Art
[0002] The development of green and renewable energy has become a top priority. As the main electrochemical energy storage system, lithium-ion batteries have been widely used in portable electronics, electric vehicles, and energy storage grids. However, with the increase in lithium costs and the depletion of lithium reserves, researchers are committed to finding alternative energy sources that can replace or partially replace lithium-ion batteries (LIBs). Sodium-ion batteries have gradually become the first choice for the next generation of energy storage systems due to their significant advantages of wide resource distribution and low cost.
[0003] In sodium-ion batteries, the cathode material is one of the key factors that determine the battery capacity, operating voltage and cost. Common cathode materials include layered oxides, polyanionic compounds, Prussian blue analogs, organic materials, etc. Among them, layered oxide cathode materials have been widely studied due to their high theoretical capacity, low cost and easy synthesis. According to the relative orientation and stacking order of adjacent metal oxide layers, layered oxide cathode materials are generally divided into P2 and O3 phases. O3-type layered oxides have high specific capacity and high energy density, and have good potential for large-scale commercial applications.
[0004] Among the many O3-type cathode materials, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 NFM is considered as one of the best choices for SIBs cathode materials due to its low cost, eco-friendliness and relatively stable structure. However, the practical application prospects of NFM are limited by two key defects. Under high voltage conditions, the electrochemical cycle curve of NFM charge and discharge process will show a long voltage platform, and the cathode material will undergo transition metal layer slip and Na + The ordered rearrangement of vacancies leads to complex phase transition problems, and its phase structure undergoes a complex evolution of O3-P3-O3′-P3′-O3 during the charge and discharge process. The complex phase transition of the material will cause damage to the crystal structure and huge volume changes, resulting in obstruction of the diffusion channel of sodium ions and the generation of mechanical cracks in the material, causing the capacity decay and cycle performance of the battery to decrease. In addition, NFM also faces the problem of slow sodium ion transport kinetics inherent in O3-type materials. For O3-type materials, due to the short distance between sodium layers, Na + The activation energy of diffusion is high, when Na + Migration from one octahedral site to another requires passing through a tetrahedral shared edge site with a high energy barrier, resulting in slow kinetics and reduced rate performance. Summary of the invention
[0005] The present invention aims at the slow Na + Diffusion kinetics and complex phase transition problems are solved, and a layered cathode material for sodium ion batteries and a preparation method thereof are provided. 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The layered sodium-ion battery positive electrode is co-doped with double metal cations to improve the material rate performance and cycle performance.
[0006] The technical solution adopted by the present invention is: The present invention discloses a sodium ion battery layered positive electrode material co-doped with Al and Zn, the chemical formula of which is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-2x Al x Zn x O 2 , where 0.01≤x≤0.06.
[0007] Preferably, the present invention provides a layered positive electrode material for sodium ion batteries co-doped with Al and Zn, the chemical formula of which is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-2x Al x Zn x O 2 , wherein 0.01≤x≤0.04, more preferably 0.015≤x≤0.03, and even more preferably 0.015≤x≤0.025.
[0008] In the present invention, the appropriate amount of Al doping strategy can improve the mechanical properties of sodium layered oxides, improve the structural strength and structural stability of the material, and reduce the degree of lattice distortion of the material during the phase change process; the appropriate amount of Zn doping strategy can make the material have relatively excellent ion diffusion performance, high voltage and high energy density advantages. Through the synergistic effect of equal proportions and appropriate amounts of Al and Zn, after the product is assembled into a battery, the capacity retention rate is greater than or equal to 73% after 200 cycles at 1C.
[0009] The present invention also provides a method for preparing the Al and Zn co-doped sodium ion battery layered positive electrode material, comprising the following steps: (1) Grinding the sodium source, the nickel-iron-manganese-based precursor, the aluminum source and the zinc source in a mortar according to a set molar ratio; (2) ball milling the crushed materials in a planetary mixer to obtain a mixed powder; (3) Under an oxidizing atmosphere, the mixed powder is first kept at 450-600 °C for 3-8 h and then kept at 850-1000 °C for 720-1200 min to obtain an O3-type layered sodium-ion battery positive electrode material.
[0010] Preferably, in step (1), the sodium source is sodium carbonate; the nickel-iron-manganese-based precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 ; The aluminum source is aluminum oxide; The zinc source is zinc oxide.
[0011] Preferably, in step (1), the particle size of sodium carbonate is less than or equal to 150 μm, preferably 100-150 μm; the nickel-iron-manganese-based precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 The particle size of is less than or equal to 20 μm, preferably 1-10 μm; the particle size of aluminum oxide is less than or equal to 200 nm, preferably 100-200 nm; the particle size of zinc oxide is less than or equal to 10 μm, preferably 0.1-10 μm.
[0012] Preferably, in step (2), the stirring and mixing time is 5 to 10 min.
[0013] Preferably, in step (3), the oxidizing atmosphere is an air atmosphere or an oxygen atmosphere.
[0014] Preferably, in step (3), the mixed powder is first heated from room temperature to 450-600°C at a heating rate of 1-2°C / min and kept at that temperature for 3-8 h, and then heated to 750-950°C at a heating rate of 3-8°C / min and kept at that temperature for 15-30 h.
[0015] Preferably, in step (3), the product is crushed to a particle size of 1-15 μm, preferably 1-5 μm, before being assembled into a battery.
[0016] The present invention adds the prepared positive electrode active material powder, carbon black and polyvinylidene fluoride (PVDF) into N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 (N-methylpyrrolidone is 3 times the mass of the positive electrode active material powder used), prepares a uniform slurry through centrifugal ball milling, and evenly coats it on aluminum foil; then transfers the aluminum foil to a blast dryer, and after drying at 80°C for 4 hours, uses a punching machine to cut into pole pieces with a diameter of 12 mm, rolls and then vacuum-dries at 110°C for 12 hours, uses a sodium metal sheet as a negative electrode, uses a glass fiber GF / D as a separator, and uses 1M NaPF 6 PC / FEC (volume ratio of 95:5) solution was used as the electrolyte to assemble CR2016 button cells in a glove box filled with argon. The assembled battery was subjected to charge and discharge cycle test in the Xinwei battery test system, with a test voltage range of 2 to 4.2V, a test condition of 200 cycles at 1C rate, and a test temperature of 25°C. The capacity retention rate of the obtained battery after 200 cycles at 1C was greater than or equal to 73%.
[0017] The beneficial effects of the present invention are as follows: (1) The raw materials of the present invention are cheap, the preparation method provided is simple, the conditions are easy to control, and it has certain commercial prospects.
[0018] (2) After element doping, the prepared material is still pure O3 phase with good crystallinity and will not change the structural characteristics of the original material.
[0019] (3) By regulating the content ratio of ion doping, the structural strength and stability of the main material can be improved, its structural degradation can be inhibited, and the phase change path can be changed. The interlayer structure and interlayer force of the layered material can be regulated, thereby improving the comprehensive electrochemical performance of the layered positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] FIG1 is a cycle performance diagram of the positive electrode materials of Example 1 and Comparative Example 1 at 1C; FIG2 is a rate performance diagram of the positive electrode materials of Example 1 and Comparative Example 1; FIG3 is a cycle performance diagram of the positive electrode materials of Example 2 and Comparative Example 1 at 1C; FIG4 is a graph showing the rate performance of the positive electrode materials of Example 2 and Comparative Example 1; FIG5 is a cycle performance diagram of the positive electrode materials of Example 3 and Comparative Example 1 at 1C; FIG6 is a rate performance diagram of the positive electrode materials of Example 3 and Comparative Example 1; FIG. 7 is a graph showing the cycle performance of the positive electrode material of Example 2 at 1C; FIG8 is a rate performance diagram of the positive electrode material of Comparative Example 2; FIG9 is a graph showing the cycle performance of the positive electrode material of Example 3 at 1C; FIG10 is a rate performance diagram of the positive electrode material of Comparative Example 3; FIG11 is an X-ray diffraction pattern of Examples 1, 2, 3 and Comparative Examples 1, 2, 3; FIG12 is a scanning electron microscope image of the positive electrode materials of Example 1 and Comparative Example 1.
[0021] In the accompanying drawings, NFM represents a battery assembled from the product obtained in Comparative Example 1, AZ1 represents a battery assembled from the product obtained in Comparative Example 2, AZ2 represents a battery assembled from the product obtained in Example 1, AZ3 represents a battery assembled from the product obtained in Example 2, AZ4 represents a battery assembled from the product obtained in Example 3, and AZ5 represents a battery assembled from the product obtained in Comparative Example 3. DETAILED DESCRIPTION
[0022] Example 1
[0023] Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.96 Al 0.02 Zn 0.02 O 2 Preparation of (x=0.02): The steps are: (I) 1.12 g sodium carbonate (particle size less than 150 μm), 1.75 g Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 The precursor (particle size is less than 20 μm), 0.02 g of aluminum oxide (particle size is 100-200 nm), and 0.33 g of zinc oxide (particle size is 0.1-10 μm) were ground in a mortar for 10 min; (II) Mix the ground powder from step (I) in a planetary mixer for 6 min at a stirring speed of 300 rpm; (III) Place the mixed powder from step (II) in a muffle furnace and heat it at 1 °C min under air atmosphere. -1 The temperature was heated to 450 °C and kept at this temperature for 300 min, and then heated at 5 °C min -1 The temperature was raised to 900 °C at a rate of 100 °C, kept at this temperature for 1200 min, and then cooled to room temperature to obtain Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.96 Al 0.02 Zn 0.02 O 2 After grinding, the positive electrode material particle size is controlled to be between 1-5 μm.
[0024] Electrochemical performance determination: The prepared positive electrode active material powder (particle size of 1-5 μm), carbon black (particle size of 8-500 nm), and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 (N-methylpyrrolidone was 3 times the mass of the positive electrode active material powder used), and a uniform slurry was prepared by centrifugal ball milling and evenly coated on aluminum foil. The aluminum foil was then transferred to a blast dryer and dried at 80 °C for 4 hours. It was then cut into 12 mm diameter pole pieces with a punching machine, rolled and dried at 110 °C for 12 hours in vacuum. Sodium metal flakes were used as negative electrodes, glass fiber GF / D was used as separators, and 1M NaPF 6 PC / FEC (volume ratio of 95:5) solution was used as the electrolyte to assemble CR2016 button cells in a glove box filled with argon. The assembled batteries were subjected to charge and discharge cycle tests in the Xinwei battery test system. The test voltage range was 2-4.2V, the test conditions were 200 cycles at 1C rate, and the test temperature was 25°C.
[0025] Comparative Example 1 Same as Example 1, except that the obtained material is O3 type NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Layered cathode materials.
[0026] FIG1 shows the cycle performance test results of Example 1 and Comparative Example 1. The capacity retention rate of Comparative Example 1 after 200 cycles at 1C is only 50.88%, while the capacity retention rate of the battery of Example 1 is increased to 73.98% after 200 cycles at 1C, and the cycle performance is significantly improved.
[0027] FIG. 2 shows the rate performance test results of Example 1 and Comparative Example 1. The rate performance of Example 1 is better than that of Comparative Example 1.
[0028] Example 2 Same as Example 1, except that the Al / Zn doping amounts of the positive electrode material prepared in step I are 3% respectively, and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.94 Al 0.03 Zn 0.03 O 2 .
[0029] FIG3 shows the cycle performance test results of Example 2 and Comparative Example 1. The capacity retention rate of the battery of Example 2 is increased to 73.46% after 200 cycles at 1C, and the cycle performance is significantly improved.
[0030] FIG4 shows the rate performance test results of Example 1 and Comparative Example 1. The rate performance of Example 2 is also better than that of Comparative Example 1.
[0031] Example 3 Same as Example 1, except that the Al / Zn doping amounts of the positive electrode material prepared in step I are 4% respectively, and the positive electrode material prepared is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.92 Al 0.04 Zn 0.04 O 2 .
[0032] FIG5 shows the cycle performance test results of Example 3 and Comparative Example 1. The capacity retention rate of the battery of Example 3 is increased to 67.46% after 200 cycles at 1C, and the cycle performance is significantly improved.
[0033] FIG6 shows the rate performance test results of Example 3 and Comparative Example 1. The rate performance of Example 3 is also better than that of Comparative Example 1.
[0034] Comparative Example 2 Same as Example 1, except that the Al / Zn doping amounts of the positive electrode material prepared in step I are 3% respectively, and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.98 Al 0.01 Zn 0.01 O 2 .
[0035] FIG7 shows the cycle performance test results of Comparative Example 2. The capacity of the battery in Comparative Example 2 is 67.51% after 200 cycles at 1C, which is relatively lower than the capacity retention rate of 73.98% in Example 1 after 200 cycles. When the Al / Zn co-doping content is low, its effect of enhancing the stability of the positive electrode material will be lost.
[0036] FIG8 shows the rate performance test results of Comparative Example 2. The capacity of Comparative Example 2 with trace Al / Zn doping is improved compared with that of undoped Comparative Example 1 under different rate test conditions.
[0037] Comparative Example 3 Same as Example 1, except that the Al / Zn doping amounts of the positive electrode material prepared in step I are 6% respectively, and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.88Al 0.06 Zn 0.06 O 2 .
[0038] FIG9 shows the cycle performance test results of Comparative Example 3. The capacity of the battery in Comparative Example 3 is 64.21% after 200 cycles at 1C, which is relatively lower than the capacity retention rate of 73.98% in Example 1 after 200 cycles. When the Al / Zn co-doping content is high, it is not conducive to the stability of the positive electrode material.
[0039] FIG10 shows the rate performance test results of Comparative Example 3. The rate performance is lost due to a high Al / Zn co-doping content.
[0040] FIG11 shows the X-ray diffraction patterns of Example 1, Example 2, Example 3, and Comparative Example 1, Comparative Example 2, and Comparative Example 3. It can be seen from the figure that Al / Zn co-doping does not change the material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The layered material has the original O3 phase structural characteristics, and each positive electrode material maintains good crystallinity.
[0041] Scanning electron microscope images were taken for Comparative Example 1 and Example 1. From FIG. 12 , it can be seen that Example 1 and Comparative Example 1 maintain the secondary particle structure composed of lamellar primary particles, indicating that Al / Zn co-doping does not change the material morphology.
Claims
1. An Al and Zn co-doped sodium ion battery layered positive electrode material, characterized in that: The chemical formula of the positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-2x Al x Zn x O2, where 0.01≤x≤0.
06.
2. The Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 1, characterized in that: The chemical formula of the positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-2x Al x Zn x O2, where 0.015≤x≤0.
03.
3. The Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 1, characterized in that: The chemical formula of the positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-2x Al x Zn x O2, where 0.015≤x≤0.
025.
4. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Grinding the sodium source, the nickel-iron-manganese-based precursor, the aluminum source and the zinc source in a mortar according to a set molar ratio; (2) mixing the crushed materials in a planetary mixer to obtain a mixed powder; (3) The mixed powder is heat treated to obtain an O3-type layered sodium ion battery positive electrode material.
5. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 4, characterized in that: In the step (1), the sodium source is sodium carbonate; the nickel-iron-manganese-based precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the aluminum source is aluminum oxide; the zinc source is zinc oxide.
6. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 4, characterized in that: In step (1), the particle size of sodium carbonate is less than or equal to 150 μm, preferably 100-150 μm; the nickel-iron-manganese-based precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The particle size of (OH)2 is less than or equal to 20 μm, preferably 1-10 μm; the particle size of aluminum oxide is less than or equal to 200 nm, preferably 100-200 nm; the particle size of zinc oxide is less than or equal to 10 μm, preferably 0.1-10 μm.
7. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 4, characterized in that: The powders in step (2) are mixed by ball milling.
8. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 4, characterized in that: The heat treatment conditions in step (3) are to keep the temperature at 450-600°C for 3-8 hours in an oxidizing atmosphere, and then keep the temperature at 850-1000°C for 720-1200 minutes, and cool the furnace after sintering.
9. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 8, characterized in that: Before the obtained product is assembled into a battery, it is crushed to a particle size of 1-15 μm, preferably 1-5 μm.
10. The method for preparing an Al and Zn co-doped sodium ion battery layered positive electrode material according to claim 4, characterized in that: The prepared positive electrode active material powder, carbon black and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 8:1:1, and N-methylpyrrolidone was 3 times the mass of the positive electrode active material powder used. A uniform slurry was prepared by centrifugal ball milling and evenly coated on an aluminum foil. The aluminum foil was then transferred to a blast dryer and dried at 80°C for 4 hours. It was then cut into 12 mm diameter pole pieces by a punching machine, rolled and vacuum dried at 110°C for 12 hours. A sodium metal sheet was used as the negative electrode, a glass fiber GF / D was used as the diaphragm, and a 1 M NaPF6 PC / FEC solution was used as the electrolyte. A CR2016 button cell was assembled in an argon-filled glove box. The assembled battery was subjected to a charge and discharge cycle test in a Xinwei battery test system. The test voltage range was 2 to 4.2 V, the test conditions were 200 cycles at a 1C rate, and the test temperature was 25°C. The capacity retention rate of the obtained battery after 200 cycles at 1C was greater than or equal to 73%.
Citation Information
Patent Citations
Double-site metal ion doped nickel iron sodium manganate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN118315567A